Action observation facilitates anticipatory control of grasp for object mass but not weight distribution. (1st April 2022) - Lee-Miller, Trevor; Gutterman, Jennifer; Chang, Jaymin; Gordon, Andrew M.
Highlights: Lift observation of a heavy box results in increased subsequent force application. Lift observation of an off-centered object does not update weight distribution. Observing larger rolls of an off-centered object leads to smaller observer rolls. Abstract: Action observation has been shown to facilitate the performance of the observer and is being increasingly used as a rehabilitation tool following neurological damage. During object manipulation, visual observation of performance is suggested to enable the updating of the sensorimotor representations of object properties. Here, through 3 experiments, we examine the effect of action observation of a novel object on the updating of object mass and weight distribution for bimanual manipulation. For each experiment, naïve participants were allocated into pairs and assigned as the "performer" or "observer". For experiments 1 and 2, observers sat opposite the performers. For experiment 3, observers stood behind the performer. The pairs observed and lifted either i) a light or heavy box in experiment 1, or ii) a box with a left or right uneven center of mass in experiments 2 and 3. Our results showed that action observation facilitated the updating of object mass information but not information about weight distribution. Specifically, observers of the heavy box subsequently applied larger forces and force rates in accord with the mass of the box. In contrast, both performers and observers of the uneven box had large peak rolls. We suggest that this shows the robustness of observation in facilitating an understanding of object mass while highlighting the complexity of manipulating an object with uneven weight distribution.